PENGEMBANGAN MEDIA SNAKE AND LADDER AUGMENTED REALITY (SLAR) PADA MATA PELAJARAN IPAS TOPIK PERKEMBANGBIAKAN TUMBUHAN DI KELAS IV SEKOLAH DASAR - Hafizah, Siti Sadiah Nur; Andriana, Encep; Syachruroji, A. (Jurnal Pendidikan Dasar, 2024)
This research and development aims to describe the development process, feasibility and students' responses to snake and ladder augmented reality (SLAR) media in the science and sciences subject on the topic of plant reproduction in class IV elementary school. This research uses the Research and Development (R&D) research method with the ADDIE development model. This research uses data collection techniques of observation, interviews, questionnaires and documentation. Data analysis was carried out through descriptive analysis based on Likert and Guttman scales with interpretation referring to Riduwan's criteria. The subjects in this research were 30 class IV students at SDN Serang 3 for the 2024/2025 academic year.  Based on the results of the product validation assessment, media expert validation obtained an average score of 86.87% with the criteria "very feasible", material expert validation obtained an average score of 91.81% with the criteria "very feasible", and language expert validation obtained an average -average score 86.25% with "very feasible" criteria. So the overall percentage of product feasibility was 88.31% with very feasible criteria and student responses obtained a percentage of 99.44% with "very good" criteria. Thus, snake and ladder augmented reality (SLAR) media in the science and sciences subject on the topic of plant reproduction in class IV elementary school is very feasible and gets a very good response from students. So the media developed is very suitable for use in the learning process in class IV elementary schools.